Stone cold - Baldacci, David (New York : Grand Central Pub., 2007)
While Oliver Stone and the Camel Club try to protect Annabelle Conroy from her mother's murderer, Stone finds men from his shadowy past turning up dead. When buried secrets are resurrected, the members of the Camel Club left standing will be changed forever.
Keywords: Stone, Oliver (Fictitious character) -- Fiction; Camel Club (Imaginary organization) -- Fiction; Secret societies -- Fiction; Swindlers and swindling -- Fiction; Casinos -- Fiction; Intelligence service -- Fiction; Murder -- Fiction; Washington (D.C.) -- Fiction; Political fiction; Suspense fiction